Virtual eulogies, rituals, and burials: Experiences of and adaptations to death and mourning during the COVID-19 pandemic among transnational families - Maviza, Gracsious; Thebe, Phillip (SAGE Publications, 2025)
This paper is based on in-depth qualitative data from key informants (i.e., village heads, and employees of burial societies) and dyads from five families interviewed between March 2020 and December 2022 in Tsholotsho and Johannesburg to explore the experiences of and adaptations to death within transnational families during the COVID-19 pandemic. This follows the extraordinary autocratic governance and weaponisation of COVID-19 and the resulting travel restrictions between Zimbabwe and South Africa. The paper finds that amid mobility constraints, families experienced sociocultural changes in relation to death, causing them to experience death and mourning in unorthodox ways. For example, they participated in online memorial, funeral, and burial services and eulogies, thus embracing transnationalism by virtually participating in funerary processes at home in Zimbabwe while based in South Africa. It concludes that these virtual rituals, while giving members an appreciated sense of togetherness, did not suffici